Occupation in areas of environmental fragility, an analysis of the Carrapicho Settlement in the city of Várzea Grande – MT - Moraes, Giovanna Erina da Silva; Ravache , Rosana Lia (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT Objective – This article examines irregular settlements in environmental preservation areas, using the Carrapicho Settlement as a case study, located in the eastern region of Várzea Grande – Mato Grosso, Brazil. The research identifies the factors that contributed to irregular occupation in the area, the resulting socio-environmental impacts, and proposes intervention strategies to mitigate risks and promote urban sustainability. Methodology – This study adopted a qualitative approach, using the case study method. By employing thematic maps, satellite images, on-site surveys, and legal analyses, an assessment of urban morphology and the interrelationship between water resources and urban space was conducted. Originality/Relevance – The study addresses the contradiction between the historical occupation of riverside areas, such as those along the Cuiabá River, and the current environmental fragility of these locations. It discusses the failure of public authorities to ensure efficient housing and environmental policies, as well as the impacts of legislative changes on preservation areas, which lead to socio-environmental degradation. Results – The study found that the Carrapicho Settlement, located on a floodplain for over 60 years, suffers from poor infrastructure, lack of basic sanitation, and environmental degradation due to irregular waste disposal and water pollution. The reclassification of the area as a Multiple-Use Zone (ZUM 1) under Complementary Law No. 4700/2021 did not resolve socio-environmental risks, while the construction of a new bridge increased pressure for irregular settlements and intensified real estate speculation. The research also highlighted the urgent need for interventions that combine sustainable land regularization, relocation of populations in high-risk situations, and the implementation of green infrastructure solutions. Theoretical/Methodological Contributions – Integration of morphological, environmental, and urban analyses to assess risk-prone areas, with a replicable model for similar studies in other locations. Critique of the loosening of urban legislation for environmental protection areas without proper socio-environmental impact planning. Social and Environmental Contributions – The study proposes integrated solutions to mitigate vulnerabilities in the Carrapicho Settlement, including the creation of an eco-neighborhood in a safe area, sustainable reurbanization projects with proper drainage, and the implementation of public green spaces. These measures aim not only to improve the quality of life for local residents but also to restore degraded areas, reduce flood risks, and promote balanced urban development, aligning housing policies with environmental preservation.